Palm Cooling Does not Improve Running Performance - Scheadler, C. M.; Saunders, N. W.; Hanson, N. J.; Devor, S. T. (International Journal of Sports Medicine, 2013)
The aim of this study was to test the efficacy of the BEX Runner palm cooling device during a combination of exercise and environmental heat stress. Twelve subjects completed two randomly ordered time-to-exhaustion runs at 75% VO2max, 30 °C, and 50% relative humidity with and without palm cooling. Time to exhaustion runs started once the warm-up had elicited a core temperature of 37.5 °C. Heart rate, Rating of Perceived Exertion, Feeling Scale, and core temperature were recorded at 2-min intervals during each run. Time to exhaustion was longer in control than treatment (46.7±31.1 vs. 41.3±26.3 min, respectively, p<0.05); however, when warm-up time was included in analysis, there was no difference between trials for total exercise time (52.5±24.2 vs. 54.5±31.4 min, respectively). The rate-of-rise of core temperature was not different between control and treatment (0.047 vs. 0.048 °C · min−1, respectively). The use of the BEX Runner palm cooling device during a run in hot conditions did not eliminate or even attenuate the rise in core temperature. Exercise time in hot conditions did not increase with the use of the palm cooling device and time to exhaustion was reduced.
Keywords: time to exhaustion; core temperature; glabrous